It's not just a piece of paper: University education signals status and personality - Costa, Tainah P. de P.; Castro, Felipe N. (Personality and individual differences, 2023)
The attribution of status carries significant social and reproductive advantages as it reflects individual qualities. However, the traits conveyed and those perceived do not always align with reality. It is crucial to understand how the status associated with different professions can influence the perception of traits, as it assists in decision-making during social interactions. This study aimed to investigate whether the status derived from university education influences the assessment of social status, mate value and personality traits among Brazilians. A quasi-experimental design with nonrandom assignment was used, employing online questionnaires administered through Google Forms. A total of 252 participants, both male and female, over 18 years of age, and residing in Brazil, took part in the study. These participants evaluated the social status, mate value, and personality traits of stimulus subjects with high and low-status university education. The results revealed that stimulus subjects with high-status university education were regarded as possessing higher status in society and scored higher on Dark Triad traits. In contrast, stimulus subjects with low-status university education were perceived as having greater agreeableness, emotional stability, and openness to experiences. In conclusion, university education signals social and personality traits, serving as a parameter to shape social perceptions. •Subjects with high-status backgrounds are rated higher on Dark Triad traits.•Low status indicates greater agreeableness, emotional stability, and openness.•University education serve as an indicator of social and personality traits.•University education affects the perception of the individuals in social hierarchy.